Life events and difficulties preceding stroke. Issue 12 (December 1990) - House, A; Dennis, M; Mogridge, L; Hawton, K; Warlow, C
Abstract : Life events and difficulties were recorded for the year before stroke, using a standardised semi-structured interview, in 113 surviving patients seen after their first ever in a lifetime stroke. An age and sex-matched control group (n = 109) was also interviewed about the preceding year. The stroke patients reported fewer non-threatening events and events with only a short-term threat, while difficulties were reported with equal frequency by the two groups. However, events which were severely threatening in the long-term were significantly more common in the stroke patients (in the 52 weeks before stroke 26% versus 13%, odds ratio 2.3, 95% confidence interval 1.1-4.9). The increased rate was apparent throughout the year and not just in the weeks immediately before stroke onset. The number of stroke patients experiencing severe events in the follow up year fell to the level found in the control group. Recognised risk factors for stroke were found equally in those patients with and without severe events before onset, except that hypertension was rather less common in the patients who had experienced a severe event. It therefore appears that severe life events may be one of the determinants of stroke onset.